Reveal the dynamics of mobile health services continuance intention: effects of expectation, confirmation, and chronic disease - Ma, Xiumei; Li, Yanxia; Suo, Ao (Frontiers in Public Health, 2025)
IntroductionThe sustainable development of mobile health (mHealth) services relies on the continuous use by users. Most studies consider users’ intention to continue using mHealth services as a static measure rather than one that changes dynamically over time, often neglecting the impact of individual differences, such as the presence of chronic disease, on usage patterns.MethodsDrawing on the expectation-confirmation model, this study investigates the dynamic nature of the intention to continue using mHealth services, with a particular focus on the role of chronic disease. Conducting a longitudinal study with three rounds of online survey, we analyzed data collected from 236 completed respondents using a latent growth model.ResultsThe results indicate that users’ intention to continue using mHealth services is not static and tends to decrease over time. Expectation accelerates the descent, while confirmation mitigates it. Furthermore, expectation shows a stronger impact on users without chronic disease compared to those with chronic conditions.DiscussionThis study advances the understanding of the continuous use of mHealth services by incorporating time-based dynamics and the influence of chronic disease. This study also extends the traditional expectation-confirmation model into a dynamic framework.